The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.6061/clinics/2013(10)03
|View full text |Cite
|
Sign up to set email alerts
|

Duration effect of desflurane anesthesia and its awakening time and arterial concentration in gynecologic patients

Abstract: OBJECTIVES:To determine the awakening arterial blood concentration of desflurane and its relationship with the end-tidal concentration during emergence from various durations of general anesthesia.METHOD:In total, 42 American Society of Anesthesiologists physical status class I-II female patients undergoing elective gynecologic surgery were enrolled. General anesthesia was maintained with fixed 6% inspiratory desflurane in 6 l min-1 oxygen until shutoff of the vaporizer at the end of surgery. One milliliter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In this study, the end-tidal concentrations of sevoflurane decreased more prominently in the initial 5 minutes after discontinuation, indicating a rapid alveolar washout, and then became consistently close to the arterial concentrations. Our previous study demonstrated that the end-tidal concentrations of desflurane are generally lower than the arterial blood concentrations during elimination in gynecologic patients 8 ; this effect is related to the lower blood-gas partition coefficient of 0.42 and tissue/blood partition coefficients of desflurane 5 . By determining the arterial blood concentration, we therefore identified that the end-tidal concentration of sevoflurane, which is close to 0.36%, is a reliable indicator for predicting emergence from general anesthesia.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, the end-tidal concentrations of sevoflurane decreased more prominently in the initial 5 minutes after discontinuation, indicating a rapid alveolar washout, and then became consistently close to the arterial concentrations. Our previous study demonstrated that the end-tidal concentrations of desflurane are generally lower than the arterial blood concentrations during elimination in gynecologic patients 8 ; this effect is related to the lower blood-gas partition coefficient of 0.42 and tissue/blood partition coefficients of desflurane 5 . By determining the arterial blood concentration, we therefore identified that the end-tidal concentration of sevoflurane, which is close to 0.36%, is a reliable indicator for predicting emergence from general anesthesia.…”
Section: Discussionmentioning
confidence: 93%
“…During the elimination phase, sevoflurane washout progresses from the brain and body to the alveolar space and can be detected by the end-tidal concentration. Clinically, the end-tidal concentration of inhalation anesthetics has been a feasible indicator for predicting the emergence from general anesthesia, especially after desflurane anesthesia 8 . However, irregular respiration before awakening usually results in fluctuations of the end-tidal concentrations of inhalation anesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the wider range of MEP amplitudes at T2 with propofol, compared to any measurement in the control group, may indicate a persistent desflurane effect. However, based on data regarding the time frame of desflurane elimination, desflurane blood concentrations should reach clinically irrelevant levels after 20 min (Lin et al, 2013;Lu et al, 2013). Moreover, the protocol requires a maximum MAC of 0.6, which suggests even faster elimination.…”
Section: Tablementioning
confidence: 98%
“…(5) For inhalational anaesthetics, however, a time lag between end-tidal and brain concentrations has been identi ed and physiologically modelled through measurement of the inspiratory, end-tidal, and jugular bulb concentrations. (6)(7)(8) Accordingly, the body's uptake and elimination (9) of anaesthetics across the alveolar membrane and blood-brain barrier depend on the partition coe cient, (10)(11)(12) ventilation, (13) and cardiac output. (7) Sevo urane requires nearly 40 min to achieve a pharmacokinetic equilibrium between arterial and jugular bulb concentrations, indicating that no further brain uptake of inspiratory 3.5% sevo urane occurs after general anaesthesia induction.…”
Section: Introductionmentioning
confidence: 99%